2019
DOI: 10.24818/mer/2019.12-07
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Job Satisfaction On Employees' Performance: A Case Study of Al Hayat Company - Pepsi Employees In Erbil, Kurdistan Region-Iraq

Abstract: The main purpose of this study was to investigate the effect of job satisfaction on employees' performance: Case study of Al Hayat Company -PEPSI employees in Erbil, Kurdistan Region -Iraq. The method of this research is descriptive-survey, in terms of nature, it is applied and also in terms of time it is cross-sectional. The statistical population of this study consisted of most employees of this company in Erbil, with a sample size of 173. The sampling method was simple random. Data were collected using two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
3
17
0
2
Order By: Relevance
“…The issue of job satisfaction has been the center of attention among academics, researchers, and practitioners because its existence is very important for organizations, especially educational organizations, including school organizations at the level of early childhood education. As shown by several studies in various organizations, industries, and country that job satisfaction proven significantly influences organizational commitment (Talasaz, Saadoldin, & Shakeri, 2017;Ćulibrk et al 2018;Yao, Qiu, & Wei, 2019), organizational citizenship behavior (Motalebi & Marşap, 2020;Moestain, Hamidah, & Kadir, 2020;Ramadhan, Saudi, & Yenni, 2018), productivity (Embuldeniya, 2017), and performance (Oravee, Zayum, & Kokona, 2018;Abdulkhaliq, & Mohammadali, 2019). Job satisfaction is a pleasurable emotional state resulting from the appraisal of one's job or job experiences, it represents how you feel about your job and what you think about your job (Colquitt, Lepine, & Wesson, 2015;Noe et al, 2015;McShane, & Von Glinow, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of job satisfaction has been the center of attention among academics, researchers, and practitioners because its existence is very important for organizations, especially educational organizations, including school organizations at the level of early childhood education. As shown by several studies in various organizations, industries, and country that job satisfaction proven significantly influences organizational commitment (Talasaz, Saadoldin, & Shakeri, 2017;Ćulibrk et al 2018;Yao, Qiu, & Wei, 2019), organizational citizenship behavior (Motalebi & Marşap, 2020;Moestain, Hamidah, & Kadir, 2020;Ramadhan, Saudi, & Yenni, 2018), productivity (Embuldeniya, 2017), and performance (Oravee, Zayum, & Kokona, 2018;Abdulkhaliq, & Mohammadali, 2019). Job satisfaction is a pleasurable emotional state resulting from the appraisal of one's job or job experiences, it represents how you feel about your job and what you think about your job (Colquitt, Lepine, & Wesson, 2015;Noe et al, 2015;McShane, & Von Glinow, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Job satisfaction was described by Nduati and Wanyoike [ 37 ] as having positive and emotional views regarding one’s work. Job satisfaction, according to Abdulkhaliq and Mohammadali [ 38 ], is one of the elements of a professional viewpoint and might be useful in keeping managing employees. The amount of happiness a person experiences as a result of their work is referred to as their level of job satisfaction [ 39 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Sánchez and Puente [ 67 ], personality, culture, and demographic traits are all personal traits that have no bearing on job satisfaction. According to Abdulkhaliq and Mohammadali [ 38 ], having children, a marriage, and academic credentials can all affect work satisfaction. Nguyen et al [ 68 ] found that there is no discernible relationship between satisfaction and any of the control factors, such as age, gender, or educational attainment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Semakin tepat posisi kerja serta tugas yang diberikan, semakin baik serta tepat waktu pembayaran gaji serta tunjangan kinerja yang diterima, serta semakin luas peluang yang didapatkan dalam rangka meningkatkan kualitas diri dapat memperbaiki kinerja pegawai, baik secara kuantitas maupun kualitas. Penelitian yang dilakukan oleh (Subagja, 2020) menyatakan bahwa kepuasan kerja berpengaruh positif dan signifikan terhadap kinerja karyawan, serupa dengan penelitian sebelumnya yang dilakukan oleh (Abdulkhaliq & Mohammadali, 2019) (Ratnasari & Sutjahjo, 2020) (Rosita & Yuniati, 2016) dimana hasil penelitian tersebut kepuasan kerja mempunyai pengaruh positif signifikan pada kinerja karyawan, yang artinya meningkatnya kepuasan kerja akan meningkatkan kinerja karyawan. H3: Kepuasan kerja mempunyai pengaruh positif dan signifikan pada kinerja karyawan Motivasi mempunyai pengaruh pada perbaikan kinerja secara berkelanjutan dengan kepuasan kerja terlebih dahulu, pegawai yang mempunyai motivasi serta kepuasan kerja yang tinggi, cenderung memiliki kinerja yang baik pada organisasi.…”
Section: Tabel 2 Indikator Kinerja Karyawan Pt Bank Rakyat Indonesia ...unclassified